Analisis Kaidah Kebahasaan Pada Teks Deskripsi Siswa Kelas IV SDN 1 Sandik Tahun Pelajaran 2020/2021 - Parameswari, Kinanti Idha; Gunayasa, Ida Bagus Kade; Asrin, Asrin (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
In the 2013 curriculum, there is a paradigm of establishing the language aspect that is the basis of the subject matter, namely text (text-based learning) which has also been adapted to the signs of the 2013 curriculum for the development of four language skills, namely listening, speaking, reading and writing skills. Compared to other skills, writing skills tend to be harder to master. This study focused on the rules of language in the text of the description of class IV students. The rules of language in the description text itself are not taught clearly by the teacher because the teacher only adheres to the existing syllabus. This then causes there are still many students who write the description text has not been following the rules of language. The study aims to identify the use of language rules in the text of the description of the work of students of grade IV SDN 1 Sandik school year 2020/2021. This type of research is qualitative descriptive. The data collection technique used is purposive sampling with documentation methods. Data analysis using miles and huberman models. The results stated that students have not been able to write the text of the description following the rules of language. This study can be concluded that overall the percentage of use of the language rules in the description text is 28.7% and falls into the category of less.